Micro- and nanoplastics in freshwater ecosystems—interaction with and impact upon bacterivorous ciliates - Bulannga, Rendani B.; Schmidt, Stefan (Frontiers in Earth Science, 2024)
The ubiquitous occurrence of microplastics and nanoplastics in aquatic environments is of major concern as these priority pollutants are readily ingested by a wide variety of aquatic organisms. Although quantitative data on the interaction of microplastics and even more so on nanoplastics in freshwater environments and their interaction with the aquatic food web are still limited, studies have nevertheless demonstrated that even micro-or nanosized plastic particles can be ingested by various members of the zooplankton functioning as primary consumers. Bacterivorous ciliates are crucial members of the microzooplankton. These fascinating microorganisms are critical components of microbial loops in freshwater environments and are essential links between different trophic levels within the aquatic food web. Ingestion of microscopic plastic particles affects the ciliate cell on a cellular and even on the molecular level. Physical and chemical characteristics such as size, density, and surface properties influence the stability, distribution, retention, transportation, and bioavailability of the microplastic particles for ingestion by ciliates. In turn, the environmental fate of microplastics and nanoplastics can affect their ecotoxicity via surface modifications, such as forming the so-called eco-corona. The consequences of the interaction of ciliates with microplastics and nanoplastics are the potential bioaccumulation of plastic particles through the food web and the possible interference of these emerging pollutants with controlling bacterial and possibly even viral abundance in freshwater environments. Due to the limited data available, studies elucidating the environmental bacterivorous ciliate-micro-/nanoplastics interaction are a priority research topic if we want to holistically assess the environmental fate and ecotoxicity of these pollutants.